The Oxford handbook of spontaneous thought: mind-wandering, creativity, and dreaming - Christoff, Kalina; Fox, Kieran C.R. (Oxford library of psychology, 2018)
Where do spontaneous thoughts come from? It may be surprising that the seemingly straightforward answers, "from the mind" or "from the brain," are in fact an incredibly recent, modern understanding of the origins of spontaneous thought. For nearly all of human history, our thoughts-especially the most sudden, insightful, and important-were almost universally ascribed to divine or other external sources. Scientific understanding of spontaneous thought has progressed by leaps and bounds in recent years, but big questions still loom: What, exactly, is spontaneous thought? How does the human brain generate, elaborate, and evaluate its own spontaneous creations? And why do spontaneous thoughts feature so prominently in mental life? This volume brings together views from neuroscience, psychology, philosophy, history, education, contemplative traditions, and clinical practice.